Multicultural competency, spirituality and self-efficacy in dealing with legal and ethical issues - Subarimaniam, Neerushah; Zakaria, Noor Syamilah; Wan Jaafar, Wan Marzuki (Universiti Putra Malaysia Press, 2020)
Multicultural competency and spirituality help trainee counselors to navigate the challenges of being a professional helper. Recently, the integration of multicultural counseling and spirituality have been proliferating in a number of research fields. Multicultural competency is one’s awareness, knowledge, and skills of various cultures. Next, spirituality is the sense of inter-connectedness with God and self-efficacy refers to individuals’ beliefs regarding their ability to accomplish tasks successfully. The purpose of this study is to examine the relationship between: (a) multicultural competency and trainee counselors’ self-efficacy in dealing with legal and ethical issues; and (b) spirituality and trainee counselors’ self-efficacy in dealing with legal and ethical issues. One hundred and forty-eight respondents from three private universities in Malaysia participated in the study through simple random cluster sampling. A total of three instruments were used to measure multicultural competency, spirituality, and self-efficacy respectively. The data were analyzed using Pearson Correlation. Correlation analyses revealed that there is a positive relationship between multicultural competency and self-efficacy. There is also a significant relationship between spirituality and self-efficacy. The coefficient of r value between multicultural competency and self-efficacy reflected a substantial relationship; while the strength of the relationship between spirituality and self-efficacy was weak. Hence, this study is vital as it provides the idea of incorporating multicultural competency and spirituality in the process of shaping counselors who eventually will be able to deal with legal and ethical issues in counseling efficaciously.